Functional Assessment of TSC2 Variants Identified in Individuals with Tuberous Sclerosis Complex. Issue 1 (11th October 2012) - Hoogeveen‐Westerveld, Marianne; Ekong, Rosemary; Povey, Sue; Mayer, Karin; Lannoy, Nathalie; Elmslie, Frances; Bebin, Martina; Dies, Kira; Thompson, Catherine; Sparagana, Steven P.; Davies, Peter; van den Ouweland, Ans; et al.
ABSTRACT Tuberous sclerosis complex (TSC) is an autosomal dominant disorder caused by mutations in the TSC1 or TSC2 genes. The TSC1 and TSC2 gene products, TSC1 and TSC2, form a complex that inhibits the mammalian target of rapamycin (mTOR) complex 1 (TORC1). Here, we investigate the effects of 78 TSC2 variants identified in individuals suspected of TSC, on the function of the TSC1–TSC2 complex. According to our functional assessment, 40 variants disrupted the TSC1–TSC2‐dependent inhibition of TORC1. We classified 34 of these as pathogenic, three as probably pathogenic and three as possibly pathogenic. In one case, a likely effect on splicing as well as an effect on function was noted. In 15 cases, our functional assessment did not agree with the predictions of the SIFT amino acid substitution analysis software. Our data support the notion that different, nonterminating TSC2 mutations can have distinct effects on TSC1–TSC2 function, and therefore, on TSC pathology.